2015
DOI: 10.1002/rcm.7309
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacteria by fatty acid profiling with direct analysis in real time mass spectrometry

Abstract: The results of this preliminary feasibility study show good precision and accuracy, and the fatty acid patterns are clearly distinctive for each of the ten species examined. The speed and ease of analysis and the high classification accuracy for this initial study indicate that DART is an effective method for bacterial fatty acid profiling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…These series of fatty acids are known to be the most common among lichens and as such, GC–MS analyses of Ophioparma ventosa demonstrated the occurrence of palmitic, linoleic, oleic and stearic acids within this lichen (Rycroft et al ., ). This supports NI‐DART‐MS adequacy for detection of fatty acids, as recently outlined (Cody et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…These series of fatty acids are known to be the most common among lichens and as such, GC–MS analyses of Ophioparma ventosa demonstrated the occurrence of palmitic, linoleic, oleic and stearic acids within this lichen (Rycroft et al ., ). This supports NI‐DART‐MS adequacy for detection of fatty acids, as recently outlined (Cody et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…46 Samples from five Gram-positive and five Gram-negative species have been analyzed without derivatization directly on a DART-TOF instrument and identified based on negative ion profiles of their fatty acids with 100% accuracy. 117 A number of techniques for analysis of volatile organic compounds (VOC) from microorganisms have been reviewed recently. 118 Alusta et al 119 have modified a similar DART-TOF MS commercial instrument for rapid VOC analysis released when a plasma jet (electric discharge) impacts whole bacterial cells.…”
Section: Ionization Methodsmentioning
confidence: 99%
“…Early on after its introduction, another API technique—direct analysis in real time (DART)—has been demonstrated as a rapid tool for microorganism identification utilizing fatty acids methyl ester profiles . Samples from five Gram‐positive and five Gram‐negative species have been analyzed without derivatization directly on a DART‐TOF instrument and identified based on negative ion profiles of their fatty acids with 100% accuracy . A number of techniques for analysis of volatile organic compounds (VOC) from microorganisms have been reviewed recently .…”
Section: Current Ms Approaches For Microbial Mixture Analysismentioning
confidence: 99%
“…Cody et al showed that DART MS fatty acid pro les distinguished between bacterial species. 38) Each of the 10 species were di erentiated with 100% classi cation accuracy by principal component analysis based on the relative quantitative and qualitative di erences in total fatty acid pro les. Notably, the bacteria used in the study belong to di erent genera.…”
Section: Chemical Ngerprinting Of Bacteria and Fungimentioning
confidence: 99%